2014
DOI: 10.1007/698_2014_329
|View full text |Cite
|
Sign up to set email alerts
|

Fungal-Mediated Biodegradation of Ingredients in Personal Care Products

Abstract: Many efforts have been devoted in developing technologies to remove emerging organic pollutants from freshwater systems. This chapter examined the applications of the environmental friendly technology based on fungal-mediated treatment for the degradation of ingredients in personal care products (PCPs), which are frequently detected at relevant concentrations in the aquatic environment. PCPs are daily-use products used in large quantity that includes several groups of substances (UV filters, preservatives, fra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 101 publications
0
8
0
Order By: Relevance
“…First–cytochromes and second–glutathione transferases. The cytochrome P450 system is a large family of enzymes, mainly monooxygenases catalyzing reactions of hydroxylation, oxygenation, dealkylation, epoxidation of C=C bonds, reduction, and dehalogenation ( Díaz-Cruz et al, 2014 ). It was shown that P450 play an indirect but crucial role in the process of clearance of cadmium and lead in filamentous fungi Phanerochaete chrysosporium belonging to the Basidiomycota phylum ( Zhang et al, 2015 ).…”
Section: Mycoremediation Mechanismsmentioning
confidence: 99%
“…First–cytochromes and second–glutathione transferases. The cytochrome P450 system is a large family of enzymes, mainly monooxygenases catalyzing reactions of hydroxylation, oxygenation, dealkylation, epoxidation of C=C bonds, reduction, and dehalogenation ( Díaz-Cruz et al, 2014 ). It was shown that P450 play an indirect but crucial role in the process of clearance of cadmium and lead in filamentous fungi Phanerochaete chrysosporium belonging to the Basidiomycota phylum ( Zhang et al, 2015 ).…”
Section: Mycoremediation Mechanismsmentioning
confidence: 99%
“…As brown rot fungi are the key degrading organisms in construction applications [ 8 ], lower efficacy against white rot fungi was not considered problematic. The tolerance of white rot fungi to isothiazolones and other organic biocides has been predominantly associated with the fact that the structure of several organic biocides is similar to lignin, which makes them easily degradable [ 63 , 64 ].…”
Section: Resultsmentioning
confidence: 99%
“…Palau's modern challenge is to balance the material and cultural needs of its people, the demands of its tourism industry, and the carrying capacity of its resources, while vigilantly monitoring and conserving the health of the environment that sustains both people and businesses (Graham & Idechong, 1998; Morrison, 2012; Jakobsson & Dragun, 2013; Burgin & Hardiman, 2015). In this context, Palau identified an emerging environmental threat that is uniquely tied to tourism – the ubiquity of sunscreen personal‐care products in outdoor recreation and coastal development (Díaz‐Cruz & Barceló, 2015; Nejumal et al, 2021). Palau represents a promising model for effective governance based on progressive and traditional policies that seeks to cultivate the prosperity of its industries for a sustainable economy as well as to conserve its highly valued natural resources (Graham & Idechong, 1998; Richmond et al, 2007; Birkeland, 2017; Wabnitz et al, 2018).…”
Section: Tourism As a Potential Threat To Biodiversity And Economic S...mentioning
confidence: 99%